Influence Of Genetic Factors, Physical Activity, Dietsmoking Habits And Stress Levels On The Incident Of Hypertension In People Of Productive Age In Seruyan Hilir Timur District, Seruyan Regency - Marhaeningsih, Marhaeningsih; Nina, Nina (Jurnal EduHealth, 2024)
Data on deaths due to hypertension in Seruyan Regency in the 2023 period was recorded at 13 people, while services for hypertension sufferers in Seruyan Regency were 16,098 people with a percentage of 32.2% of 49,930 people, while services for hypertension sufferers in Seruyan Hilir Timur District were 2,838 people (64 .9%) from 4,370 people. Then health services in the productive age of Seruyan Hilir Timur District for all diseases amounted to 5,269 people with a percentage of 82.5% of 6,385 people. This study aims to determine the influence of genetic factors, physical activity, diet, smoking habits and stress levels on the incidence of hypertension. This research uses a quantitative approach with a cross sectional method. The sample for the study was taken from 10% of the population, namely 107 people from the people of Seruyan Hilir Timur District, Seruyan Regency using a systematic random sampling technique. The results of the research show that there is an influence between genetic factors and smoking habits, while physical activity, diet and stress levels have no effect on the incidence of hypertension in people of productive age in Seruyan Hilir Timur District, Seruyan Regency, with the most dominant factor being the genetic factor (Exp value (B ) or Odds Ratio (OR)=10.474). The Kuala Pembuang II Community Health Center, Seruyan Hilir Timur District, Seruyan Regency is expected to be able to pay more attention and provide education to people of productive age with genetic factors and smoking habits as an effort to prevent early or reduce the risk of complications, and the Seruyan District Health Service is expected to make policies and be able to collaborate with Puskesmas Puskesmas to create classes for people of productive age with a monthly meeting program so they can monitor blood pressure and provide education in keeping their blood pressure stable at every Posyandu activity carried out every month.